Issues of Introducing Artificial Intelligence Technologies into Cassation Proceedings in Criminal Cases - Temirov Abbosjon Omonovich (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
In today's conditions of globalization, digital technologies are widely implemented in all spheres around the world and are rapidly penetrating the way of life of humanity. It can be observed that countries that are carrying out effective work in this direction are developing rapidly. In particular, in our country, digital technologies have been widely introduced into the judicial system, which serve to increase the transparency and effectiveness of criminal proceedings and ensure effective interaction between judicial bodies at various levels.